Language, identity, and survival: an ethnographic study on the revitalization of the Limola language in South Sulawesi - Hakim, M. Nur; Hidayat, Wahyu; Jusrianto, Jusrianto (Frontiers in Sociology, 2025)
The Limola language, spoken in Sassa Village, Luwu Utara Regency, South Sulawesi, represents an essential cultural identity and intangible heritage element. However, its transmission has declined due to generational language shift, placing it at risk of endangerment. This study explores the roles of community actors and strategies in revitalizing the Limola language across traditional, domestic, and digital domains. Using a qualitative ethnographic approach, data were collected through in-depth interviews with native speakers, participatory observation during traditional rituals, and documentation of digital content initiatives. Thematic analysis was applied to identify patterns of language use and preservation practices. The findings reveal that the Limola language plays a central role in various traditional rituals, such as funeral ceremonies, harvest festivals, and Mopacci, while still used to a limited extent in everyday communication. Traditional leaders maintain Limola through ritual use, native speakers—particularly elders—serve as intergenerational transmitters in family contexts, and youth utilize social media to promote the language creatively. This multi-domain revitalization approach integrates cultural traditions with modern technological adaptation, contributing to language vitality while strengthening community identity. The results highlight the theoretical significance of language as symbolic capital, the practical value of community-led digital engagement, and the policy need for formal support in education and cultural heritage recognition. This study recommends sustaining language revitalization through integrated, participatory strategies that combine ritual, domestic, and digital practices.